Silicon microwire arrays decorated with amorphous heterometal-doped molybdenum sulfide for water photoelectrolysis. (February 2017) - Chen, Chih-Jung; Yang, Kai-Chih; Liu, Chi-Wei; Lu, Ying-Rui; Dong, Chung-Li; Wei, Da-Hua; Hu, Shu-Fen; Liu, Ru-Shi
Abstract: Silicon is a promising photocathode material for solar hydrogen evolution because of its small band gap, negative conduction band position, and ideal theoretical current density. In this study, p-type Si microwire ( p -Si MW) arrays were prepared as photocathodes because of the large surface area and high light-harvesting capability. However, Si MWs suffered from low photocatalytic activity because of slow photo-induced carriers during driving of water-splitting reaction. Therefore, molybdenum sulfide (MoS2 ) with appropriate band alignment with p-Si material was employed for surface modification to function as a co-catalyst for collecting photo-generated minority carriers and reducing recombination possibility. The onset potential and current density at 0 V versus reversible hydrogen electrode (RHE) of Si@MoS2 MWs were +0.122 V and −8.41 mA cm −2 . Heterometal atoms were employed to dope MoS2 co-catalyst and expose more sulfur-terminated active sites to further boost photoelectrochemical performance. Optimal activity of Si@MMoSx (M = Fe, Co, Ni) was achieved by doping Co heteroatoms, and its turn-on voltage and photocurrent density at 0 V (vs. RHE) were respectively increased to +0.192 V and −17.2 mA cm −2 . X-ray absorption spectroscopy was applied to demonstrate that Fe ions of FeMoSx were dichalcogenide materials, forming a composite with MoS2 and contributing better photoelectrolytic efficiency. By contrast, two-valent heteroatoms of CoMoSx and NiMoSx substituted the Mo 4+ ions in MoS2 . For charge compensation, more defects and edges were revealed as active sites of solar hydrogen production by adding Co or Ni dopants in MoS2 co-catalyst, which led to lower overpotential. Graphical abstract: Highlights: MoS2 and MMoSx (M = Fe, Co, Ni) co-catalyst was modified on a Si photoabsorber to accelerate the kinetics of photoinduced carriers and reduce the recombination probability. The hydrogen evolution rate of optimal Si@CoMoSx photocathode was approximately 3.86 µmol min −1 and a Faradaic efficiency reaching 81.0%..